2003
DOI: 10.2741/1040
|View full text |Cite
|
Sign up to set email alerts
|

Thermal chronobiology of domestic animals

Abstract: This article reviews the literature on the circadian and estrous rhythms of body temperature in farm animals. Although most research in this area has lacked the methodological sophistication of research conducted on laboratory animals, the experimental results are consistent with the general principles of thermal chronobiology derived from laboratory studies and, at the same time, provide specific information about the peculiarities of livestock species. Detailed knowledge of the normal parameters of the body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 51 publications
(44 reference statements)
1
3
1
1
Order By: Relevance
“…The present result is in contrast with the finding of Picconne et al [3], who obtained a peak in foot temperature six and 13 hours before RT in sheep kept under cold condition (9°C) and themoneutral zone (25°C), respectively. Our result also disagrees with the finding in humans that foot and core temperatures attained their peaks at 12 h apart [3738]. The finding that BST, especially the feet temperature, peaked several hours before RT suggests that the mechanism of thermoregulation in the feet may be involved in production of the oscillation in RT as earlier suggested [3538].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present result is in contrast with the finding of Picconne et al [3], who obtained a peak in foot temperature six and 13 hours before RT in sheep kept under cold condition (9°C) and themoneutral zone (25°C), respectively. Our result also disagrees with the finding in humans that foot and core temperatures attained their peaks at 12 h apart [3738]. The finding that BST, especially the feet temperature, peaked several hours before RT suggests that the mechanism of thermoregulation in the feet may be involved in production of the oscillation in RT as earlier suggested [3538].…”
Section: Discussioncontrasting
confidence: 99%
“…In both studies in sheep and goats mentioned above and in the current study, the highest amplitude of daily rhythmicity of RT values was recorded when AT oscillated about 20°C, which is also similar to the finding of Lovegrave and Heldmaier [36]. The amplitude of daily rhythmicity of BST obtained at various sites in the present study was between 3 – 7°C, which was greater than the amplitude values of 0.5 – 1.3°C in sheep [37]. The differences in the amplitudes may be due to variations in animal species and AT.…”
Section: Discussionsupporting
confidence: 89%
“…Of the parameters measured, the PCV and lymphocyte counts had the greatest amplitude, while the lowest amplitude was recorded in TP, apparently because the TP did not exhibit any rhythm or variability. It has been shown that greater amplitude is accompanied by a reduction in mesor [ 4 ]. In the present study, haematological parameters with larger values tended to have greater amplitude, while those with smaller values had the tendency to have lower amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The circadian system has been extensively studied in mammals [ 4 5 ]; however, in poultry such studies are limited [ 6 7 ]. The avian circadian system is more complex than that of mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In thermoneutraler Umgebung liegt die physiologische Körpertemperatur des Rindes zwischen 38,0 und 39,2°C [8]. Fieber, indikativ für einen krankhaften Zustand, wird von verschiedenen Autoren als Anstieg der Körpertemperatur über einen Grenzwert von 39,4-39,7°C definiert [9] [10].…”
Section: Introductionunclassified